Soft X‐ray characterization of ion beam sputtered magnesium oxide (MgO) thin film. (10th May 2018) - Sinha, Mangalika; Gupta, Mukul; Jonnard, Philippe; Modi, Mohammed H.
Abstract : In the present study, surface and interface characterization of magnesium oxide (MgO) thin film is carried out by using non‐destructive soft X‐ray reflectivity and absorption technique. To get a further insight about the in‐depth and surface composition, secondary ion mass spectroscopy measurement is also carried out. The analysis of the reflectivity data indicates the presence of Mg‐Si‐O layer between the principal layer (MgO) and Si substrate interface. The secondary ion mass spectroscopy spectra corroborate well with the model assumed in the analysis of the reflectivity data. Combined soft X‐ray reflectivity‐total electron yield result confirms the presence of low‐density MgO on top of principal MgO layer. Total electron yield result confirms the rocksalt structure of the film and provides a glimpse of the electronic structure near the O‐K absorption edge.